2015
DOI: 10.1111/ases.12187
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of 15 consecutive patients who underwent laparoscopic insulinoma resection: The usefulness of monitoring intraoperative blood insulin during laparoscopic pancreatectomy

Abstract: Complete removal of an insulinoma can be reliably predicted by intraoperative blood insulin monitoring even in laparoscopic pancreatectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated that intraoperative insulin monitoring can reliably evaluate the complete removal of insulinomas (21,30). However, these studies mainly described the application of insulin level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that intraoperative insulin monitoring can reliably evaluate the complete removal of insulinomas (21,30). However, these studies mainly described the application of insulin level.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to achieve symptomatic improvement after resection has been associated with worse recurrence-free survival (RFS) (20). Considering these points together, surgeons should con rm resection outcomes after the surgical procedure (21).…”
Section: Introductionmentioning
confidence: 99%
“…When insulinomas were considered separately, the mean detection rate of EUS was 86% (range 57-100) in 12 studies including 250 patients [63,64,72,[77][78][79][80][81][82][83][84][85] and that of IOUS was 92% (range 84-100) in 9 studies including 264 patients [66,75,76,[86][87][88][89][90][91] . For duodenal tumors and lymph node metastases, the detection rate of US was 18% in a study of 25 patients [66] and that of EUS 63% in 2 studies comprising 59 patients [66,72] .…”
Section: Sensitivity Specificity and Detection Ratesmentioning
confidence: 99%
“…Once all tumor tissue is successfully removed, blood glucose should increase by approximately 30 mg/dL within 30 min and plateau after about 60 min [ 56 ]. Correspondingly, the blood insulin level should sharply fall within 30 min after tumor resection [ 57 ].…”
Section: Intraoperative Localizationmentioning
confidence: 99%